Peran Penyuluhan Dalam Pemberdayaan Petani Kelapa Sawit Pola Swadaya di Kecamatan Bonai Darussalam Kabupaten Rokan Hulu - Tian Hadi Syahputra; Roza Yulida; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objectives of the research are: (1) to determine the role of agricultural extension upon independent small holder farmers of palm oil, (2) to figure out the empowerment level the farmers, and (3) to analyze the influence of the extension’s role upon the farmers’ empowerment. The research was carried out in sub district of Bonai Darussalam Rokan Hulu district. 45 farmers were selected by using purposive sampling method and were interviewed as the respondents as well. Validity and reliability analysis have been done upon questionnaire. To answer the objective 1 and 2, analysis of Likert Scale Summated Rating (SLR) was utilized and in order to answer the objective 3, multiple regression analysis was used. The results shows: (1) The role of extension has shown quite significant role in the activities of the farmers, which consist of the role of extension as education, the dissemination of information/innovation, facilitation, consultation, supervision, monitoring and evaluation; (2) the empowerment level of the farmers is well enough consisting of a non-human resource, productive economy, and institutional; (3) the role of extension that has significant influence upon the farmers empowerment is the role extension as evaluation, meanwhile the role of extension as a education, dissemination, facilitation, consultation, and supervision have no significant influence. Keywords: The role of extension, empowerment, independent small holder farmers of palm oil, oil palm